Status of Education In Backward Community In Haryana: a Survey Study: Exploring the educational challenges faced by the backward community in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Specifically thisstudy was designed to study the education among backward community in HARYANA.Education of the backward community was examined with two perspectives, namely,backwardness and advancement. There are many facts to the concept ofbackwardness. Backwardness of a community or group implies that it lags farbehind others or criteria considered important. In considering OBCs asbackward, therefore, there is an implicit juxtaposition of the inferiorsituation of those who belongs to these castes as against the relativelyadvantageous position of upper caste Hindus. Also implicit is the assumptionthat the inferiority of the OBCs is largely a consequence of their low socioeconomic position. The low socio-economic status and low position in the castehierarchy lead to other disadvantages and disabilities such as poor access toeducation, low motivation for education, low educational aspiration, absence ofopportunity for occupational mobility etc.